Pengaruh Pendapatan Dan Gaya Hidup Terhadap Perilaku Konsumtif Petani Kelapa Sawit di Desa Karang Berahi Kecamatan Pamenang Kabupaten Merangin - Asih Tri Utami Ningsih; Addiarrahman; M. Taufik Ridho (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
In the current era of globalization, most of Karang Berahi Village's income and lifestyle are not in accordance with consumptive behavior because income and lifestyle greatly influence the consumptive behavior of oil palm farmers in Karang Berahi Village so that on average people waste more in their lifestyle. luxurious. The aim of this research is to find out how income and lifestyle influence palm oil consumptive behavior in Karang Berahi Village, Pamenang District, Merangin Regency. The method used in this research is quantitative research. Data collection was carried out by means of observation, interviews, documentation and questionnaires. This research used a sample of 85 samples. The data analysis used in this research is, validity test, reliability test, classical assumption test, descriptive statistical test, and multiple linear regression test, namely the coefficient of determination test, T test and F test. Based on the data processing carried out in this research, results were obtained for the income variable (X1) partially, namely with a significance level smaller than 0.05, namely with a significance level of 0.000, so it can be said that the income variable has a significant influence on consumer behavior. Meanwhile, for the Lifestyle variable (X2), partially, with a significance level greater than 0.05, namely with a significance level of 7.937, it can be said that the income variable has no effect on consumer behavior. Furthermore, by using the F test to obtain a significance value of 0.001 which is smaller than 0.05, the regression model can be used to predict that income and lifestyle together influence consumer behavior. The calculation of the coefficient of determination results in showing that all independent variables, namely income (X1), lifestyle (X2), can explain the consumptive behavior variable (Y) by 20%, the remaining 80% is influenced by other variables not examined in this research.